Structural integrity analysis of the pre-stressed concrete dome of the Belgrade fair hall 1 (Fracture and Structural Integrity, 2023)
Belgrade fair hall 1 is well known for its dome, which is still the world largest self-supported construction made of pre-stressed concrete, with its diameter of 106 m. In this paper the Finite Element Method (FEM) was performed to analyze different loading and supporting conditions. At the same time, crack growth in a support column was simulated by the extended FEM (XFEM). Results of numerical calculations indicate ingenious design of such a complex structure which was based on “hand” calculation decades ago, without computers. In addition to classical engineering and more advanced numerical calculations, risk based analysis was performed taking into account artificially introduced crack and Failure Analysis Diagram, obtained using stress intensity factor and net stress, as well as fracture toughness and critical stress. This analysis, made for the first time for Belgrade fair hall 1, proved that its structural integrity is jeopardized only when a crack reaches half the thickness of a steel bar.
Keywords: Belgrade Fair Hall 1; Structural Integrity; Pre-stressed concrete; Numerical simulation